1995
DOI: 10.1097/00001888-199508000-00015
|View full text |Cite
|
Sign up to set email alerts
|

What makes a tutor effective? A structural-equations modeling approach to learning in problem-based curricula

Abstract: The results suggest that subject-matter expertise; a commitment to students' learning and their lives in a personal, authentic way; and the ability to express oneself in the language used by the student are all determinants of learning in problem-based curricula. The theory of the effective tutor, presented in this article, merges two different perspectives prevalent in the literature. One perspective emphasizes the personal qualities of the tutor: his or her ability to communicate with students in an informal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
359
3
19

Year Published

1996
1996
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 327 publications
(393 citation statements)
references
References 0 publications
12
359
3
19
Order By: Relevance
“…The first line of inquiry investigates whether students in PBL classrooms learn as much as students in classrooms with traditional instruction. This research has demonstrated children and young adults in PBL classrooms can learn at least as much as other students if the problems are carefully constructed around content objectives (Davis, Oh, Anderson, Gruppen, & Nairn, 1994;Gallagher & Stepien, 1996;Goodnough & Cashion, 2003), thoughtfully delivered (Schmidt & Moust, 1995;Van Berkel & Dolmans, 2006), and appropriately scaffolded (Belland, 2010;Gallagher, 2009a;Hmelo-Silver, 2004;Hmelo-Silver, Duncan, & Chin, 2007;Vardis & Ciccarelli, 2008).…”
Section: S a Gallagher And J J Gallaghermentioning
confidence: 96%
See 1 more Smart Citation
“…The first line of inquiry investigates whether students in PBL classrooms learn as much as students in classrooms with traditional instruction. This research has demonstrated children and young adults in PBL classrooms can learn at least as much as other students if the problems are carefully constructed around content objectives (Davis, Oh, Anderson, Gruppen, & Nairn, 1994;Gallagher & Stepien, 1996;Goodnough & Cashion, 2003), thoughtfully delivered (Schmidt & Moust, 1995;Van Berkel & Dolmans, 2006), and appropriately scaffolded (Belland, 2010;Gallagher, 2009a;Hmelo-Silver, 2004;Hmelo-Silver, Duncan, & Chin, 2007;Vardis & Ciccarelli, 2008).…”
Section: S a Gallagher And J J Gallaghermentioning
confidence: 96%
“…The strongest and most consistent finding in this branch of research is that students in PBL classrooms find learning more motivating, engaging, and satisfying (e.g., Faessler, Hinterberger, Dahinden, & Wyss, 2006;Hmelo-Silver, 2004;Lieberman, Stroup-Benham, Peel, & Camp, 1997;MacKinnon, 1999;Maxwell, Bellisimo, & Mergendoller, 2001). The engagement students experience in PBL leads to achievement as evidenced in structural equation models where student engagement contributes both directly and indirectly to achievement (Van Berkel & Dolmans, 2006;Schmidt & Moust, 1995). At least part of this achievement seems to be the situational interest aroused by the problem itself.…”
Section: S a Gallagher And J J Gallaghermentioning
confidence: 99%
“…A review of recommendations for optimal tutor characteristics within PBL literature is often confusing, with some recommendations being closely overlapped while others offer direct contradictions. For example, some researchers recommend that tutors be content experts or faculty with facilitation training (Barrows, 1996;Bochner et al, 2002;Gilkison, 2003;Schmidt & Moust, 1995;Schmidt, Van Der Arend, Moust, Kokx, & Boon, 1993;Schmidt et al, 1994). An early effort that characterizes the impacts of tutor expertise in relation to faculty direction of students (Albanese & Mitchell, 1993) found that expert tutors provide less engagement for student-directed discussion and learning (Davis, Nairn, Paine, Anderson, & Oh, 1992;Silver & Wilkerson, 1991) and were more likely to intervene in student-directed discussion (De Volder, 1982).…”
Section: Tutor Content Expertisementioning
confidence: 99%
“…Previous literature has identified that PBL tutors found knowing when to intervene in the PBL process to be problematic (Kaufman & Holmes 1996;Neville 1999). Schmidt (1990) discussed the need for the tutor to learn to tolerate silence, rather than intervening to fill in the gaps in the students' discussions. Wilkerson and Maxwell (1988) highlighted the need to remain silent for prolonged periods.…”
Section: Intervening In the Pbl Processmentioning
confidence: 99%